Об условных сопротивлениях электроцепей при полигармонических входных сигналах - Божко, А.Е. (Видавничий дім "Академперіодика" НАН України, 2007)
The formulas for the conditional resistances of circuits with RL, RC, RLC, R(LIIC) elements under polyharmonic input signals are obtained.